PENGARUH LINGKUNGAN KELUARGA DAN LINGKUNGAN SEKOLAH TERHADAP PRESTASI BELAJAR SISWA EKONOMI KELAS XI IPS SMU N 10 KOTA JAMBI - Harbeng Masni, Lili Andriani, (SJEE (Scientific Journals of Economic Education), 2017)
AbstrakThe environment always revolves around the human from the time of birth until death, so that between the environment and humans there is a reciprocal relationship in the sense that the environment affects humans and humans affect the environment. So is the new as a whole, as its own experience in interaction with its environment ". Understanding the above learning emphasizes that learning is an experience and experience that one of them obtained thanks to the interaction between a person with his environment. According to psychologists, the environment that contributes greatly to the learning process and the development of children is the family environment.